A facile modification of steel mesh for oil–water separation. (3rd July 2017) - Varshney, Priya; Nanda, Debasis; Satapathy, Mitra; Mohapatra, Soumya S.; Kumar, Aditya
Abstract : A durable and regenerable superhydrophobic and superoleophilic steel mesh surface is synthesized, showing excellent oil–water separation applications. Abstract : The development of a superhydrophobic and superoleophilic steel mesh surface, which is durable and regenerable under aggressive conditions, has raised tremendous interest in oil–water separation applications. In this work, via a facile chemical etching method using a mixture of hydrochloric acid and nitric acid followed by treatment with lauric acid, a superhydrophobic and superoleophilic steel mesh surface was synthesized. The surface morphology analysis shows the presence of rough microstructures on the coated steel mesh surface. The coated mesh exhibited superhydrophobicity, with a water contact angle of 171 ± 4.5° and a sliding angle of 4 ± 0.5°, and superoleophilicity, with an oil static contact angle of about 0°, that caused water to run off the mesh while allowing oil to permeate through it. Petroleum ether–water and benzene–water mixtures were successfully separated via a simple filtering method using the coated mesh with a separation efficiency of more than 99%. Additionally, the coating was found to be mechanically, thermally and chemically stable and regenerable. Furthermore, the water-drop impact dynamics for the coated mesh surface were also studied. The aforementioned properties of the durable coated steel mesh show that it is a good candidate for facile, fast, and repeatable oil–water separation applications.